Herramienta digital Graspable Math en el aprendizaje de ecuaciones de primer grado - Sapallanay Gómez, Ninna Nyberg (2023)
The research began with the objective of evaluating the effectiveness of the digital tool Graspable Math in the process of learning first-degree equations among first-grade students of the Francisca Diez Canseco Educational Institution of Castilla de Huancavelica. The study adopted a quantitative approach, applied type, explanatory level and pre-experimental design that involved 26 students from the 1st grade of secondary school. The main results are that initially the majority of the students were at the beginning level, with 73%, while 27% were at the process level, with an average grade of 8.385. However, after implementing the effectiveness of the Graspable Math digital tool, a positive impact was observed, as the majority of students achieved the expected level of achievement, with an average grade of 15.557. It is concluded that the use of Graspable Math had a positive and significant influence on the learning process of first degree equations among the 1st grade students of the Educational Institution of the study sample.